Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 5 Polynomials and Polynomial Functions - 5.7 Apply the Fundamental Theorem of Algebra - 5.7 Exercises - Skill Practice - Page 384: 29



Work Step by Step

We need to write down the polynomial $f(x)$ in factored form. $f(x)=(x+4)(x-1)(x-2+\sqrt 6)(x-2-\sqrt 6)$ $=(x^2+3x-4)(x^2-4x+4-\sqrt{36})$ $=(x^2+3x-4)(x^2-4x-2)$ $=(x^2+3x-4) \times (x^2)-4x(x^2+3x-4)-2 \times (x^2+3x-4)$ $=x^4-4x^3-2x^2+3x^3-12x^2-6x-4x^2+16x+8$ $=x^4-x^3-18x^2+10x+8$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.